2006
DOI: 10.1111/j.1365-3156.2006.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in three consecutive mass drug administrations in Leogane, Haiti

Abstract: Summaryobjectives In the global effort to eliminate lymphatic filariasis, mass drug administrations (MDAs) are organised annually. The success of this strategy depends on achieving high levels of drug coverage, which reduce the number of persons with circulating microfilariae and consequently transmission. Persons who consistently fail to participate in MDAs represent a potential threat to the goal of filariasis elimination. We wanted to know the drug coverage, the proportion of persons who were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 7 publications
2
56
0
1
Order By: Relevance
“…It was also apparent from the participants' sentiments that knowledge about the consequences of the disease enhanced compliance. Similarly, a study done in Leogane, Haiti Mathieu et al, [21] found that persons who knew that LF was transmitted by mosquitoes were more likely to have participated in MDA than persons who did not. However, generally the study populations had relatively low levels of knowledge of cause of LF.…”
Section: Discussionmentioning
confidence: 95%
“…It was also apparent from the participants' sentiments that knowledge about the consequences of the disease enhanced compliance. Similarly, a study done in Leogane, Haiti Mathieu et al, [21] found that persons who knew that LF was transmitted by mosquitoes were more likely to have participated in MDA than persons who did not. However, generally the study populations had relatively low levels of knowledge of cause of LF.…”
Section: Discussionmentioning
confidence: 95%
“…Other investigators have grappled with this problem. 8,9 It is expensive to provide supplemental rounds of MDA to entire populations in hopes of treating people who have been missed in the early rounds. Additional rounds of MDA after rounds 4 or 5 mostly treat people who do not need further treatment and miss most of the systematically noncompliant population.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models that simulate LF transmission 3,4 and GPELF guidelines emphasize the importance of achieving high MDA coverage rates. 5,6 Reported MDA coverage rates vary, [7][8][9] and compliance rates (percentage of people who report having taken the medications) are sometimes much lower than coverage rates (percentage of people who received the medications) reported by public health authorities. 10 Compliance rates have decreased after several rounds of MDA in some areas 11 but have increased in others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poderiam ser lembrados o hábito social de ingesta alcoólica e a precocidade do trabalho; a questão da paridade, na fase etária estudada, pois a gestante deve ser excluída do processo até o ano seguinte e, nesse meio tempo, se não houver um controle de busca ativa, poderá estar novamente grávida no próximo tratamento em massa e, assim, ser excluída do processo novamente. O conhecimento desses dados e o planejamento adequado para garantir o tratamento do indivíduo faltoso, assegurando a cobertura mínima, pode influenciar o sucesso ou o fracasso em interromper a transmissão ao longo dos 5-6 anos de tratamento antifilarial em massa 17 .…”
Section: Resultsunclassified